External fire-escape stairs risk analysis: A case study in Istanbul - Avlar, Erkan; Korkmaz, Ezgi; Yildirim, Husniye Sueda (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2022)
External fire escape stairs are used in many countries. They are recognised as building elements that can minimise loss of life in case fire safety precautions are inactive or inadequate. However, external fire escape stairs pose more risk than fire exit stairs, and they have characteristics that pose hazards during access or usage in terms of fire safety. A pilot study conducted in 10 districts of Istanbul showed that the risks are high in external fire escape stairs in the city. According to the results of this study, the districts with the highest number of hazard sources on the external fire-escape stairs are Beyoglu, Besiktas, and Sisli. The aim of this study is to reveal the risks related to fire safety and to prevent or reduce the harm that these risks may cause to users by reviewing the physical conditions of the fire escape stairs in the buildings in the three districts of Istanbul, where the number of hazard sources is the highest, in order to ensure that escape from the buildings in fires is both easy and fast and does not pose a danger to the safety of the user. In this context, using a model consisting of three stages a case study was carried out in the Sisli, Besiktas, and Beyoglu districts of Istanbul. Data on hazard sources were collected in a total of 600 buildings, including 200 buildings with external fire-escape stairs in each of the three districts where the case study was conducted. The risks that may be experienced in the fire escape stairs in these districts were analysed, the results of the analysis were discussed and district-based risk maps were created. The number of hazard sources questioned in the pilot study was increased by new hazard sources identified in the research project. According to the results of the analysis study, a total of 3,580 hazard sources were determined in the interrogation conducted on 18 hazard sources. Among the three districts, the district with the highest risk value is Beyoglu and the district with the lowest is Besiktas. In these districts, necessary actions are decided and recommendations are developed to control the risks and eliminate or reduce the effects of the hazard sources on the users.
Keywords: A case study in Istanbul; external fire-escape stairs; fire escape; fire safety; Architecture